DFT investigation of O2 and PH3 adsorptions on group 8B metal˗doped boron nitride nanotubes - Sripadung, Ployvadee; Nunthaboot, Nadtanet; Wanno, Banchob (Progress in Applied Science and Technology, 2018)
The adsorptions of O2 and PH3 molecules on boron nitride nanotube (BNNT) with and without the doping of group 8B metals (TM) i.e. Fe, Ru, Os, Co, Rh, Ir, Ni, Pd, and Pt were investigated using a density functional theory calculation at the B3LYP/LanL2DZ theoretical level. The structural and electronic properties and adsorption abilities for the most stable configuration of gas adsorption on pristine and TM–doped BNNTs were calculated. The results indicate that the O2 and PH3 molecules show much stronger adsorption on the TM–doped BNNTs than that on the pristine BNNT. From our calculations, it is clearly imply that pristine BNNT is not suitable for gas sensing, while the OsB–BNNT displays the highest interaction for O2 adsorption and the PtB–BNNT displays the highest interaction for PH3 adsorption. The electronic properties such as the energy gap, partial charge transfer, and density of state of TM–doped BNNTs are significantly modified after adsorptions. In conclusion, the TM–doped BNNTs can be used as O2 and PH3 gas storage and sensing in manufacturing raw materials.